Novel biosensor system model based on fluorescence quenching by a fluorescent streptavidin and carbazole‐labeled biotin. Issue 10 (12th May 2016) - Zhu, Xianwei; Shinohara, Hiroaki; Miyatake, Ryuta; Hohsaka, Takahiro
Abstract : In the present study, a novel molecular biosensor system model was designed by using a couple of the fluorescent unnatural mutant streptavidin and the carbazole‐labeled biotin. BODIPY‐FL‐aminophenylalanine (BFLAF), a fluorescent unnatural amino acid was position‐specifically incorporated into Trp120 position of streptavidin by four‐base codon method. On the other hand, carbazole‐labeled biotin was synthesized as a quencher for the fluorescent Trp120BFLAF mutant streptavidin. The fluorescence of fluorescent Trp120BFLAF mutant streptavidin was decreased as we expected when carbazole‐labeled biotin was added into the mutant streptavidin solution. Furthermore, the fluorescence decrease of Trp120BFLAF mutant streptavidin with carbazole‐labeled biotin (100 nM) was recovered by the competitive addition of natural biotin. This result demonstrated that by measuring the fluorescence quenching and recovery, a couple of the fluorescent Trp120BFLAF mutant streptavidin and the carbazole‐labeled biotin were successfully applicable for quantification of free biotin as a molecular biosensor system. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The biotin is close to the Trp120 of the neighbor subunit in the streptavidin‐biotin complex. In this study, BODIPY‐FL‐Aminophenylalanine (BFLAF) was incorporated at the Trp120 position to product a fluorescent mutant streptavidin. The Trp120BFLAF was certainly quenched by carbazole‐labeled biotin when the Trp120BFLAF‐biotin complex was formed. Whereas in the presence of biotin existing in the solution, the Trp120BFLAF would not be quenched because of the competitive binding reactions of biotin and carbazole‐labeled biotin to the Trp120BFLAF.